Methods for reducing asymmetry in electrical networks of 0,4–10 kV - D. Yu. Rudy; A. I. Antonov; T. V. Gonenko; V. I. Kleutin; A. A. Ruppel; E. Yu. Ruppel (Омский научный вестник)
The article describes the processes associated with the appearance of asymmetry of the three-phase voltage system, the reasons why this phenomenon is undesirable are explained. The main reasons for the appearance of asymmetry in electrical networks and effects that asymmetrically stress the electrical equipment and the energy system as a whole are considered. The issues of lowering the voltage asymmetry ratio in reverse order by different methods are considered and the main recommendations are given, which allows improving the quality of electric power to meet the requirements of GOST 32144-2013. In conclusion, it is noted that at the moment the problem of voltage asymmetry requires an immediate solution, since the 0,4–10 kV electric networks are characterized by a considerable asymmetry of voltages.